Contracting with Private Information - Marcus Hagedorn (Institute for the Study of Labor (IZA), 2003)
This paper adds to the current literature on incomplete contracting that argues that deviating from a complete information, transaction-cost free environment may be may generate valuable insights. We achieve this by assuming bargaining with asymmetric information. We consider the consequences of asymmetric information for investment decisions and for the assignment of property rights. This analysis is crucial since any foundation must ensure that results of the kind derived by Grossman, Hart and Moore still hold. It is shown that investment incentives are guided by an additional element to standard hold-up models since the outcome of bargaining depends directly on the investment level. This may for example result in cooperative overinvestment. Although investment incentives are always positive from a social perspective, they can be negative from an individual's perspective. In our model, property rights are shown to still play a role. This arises from their tight interaction with ex-post bargaining. Optimal ownership structures are characterized and a new role for option contracts is identified.
Keywords: D82; D81; D23; L14; 330; private values; ownership; property rights; incomplete contracts; hold-up; Unvollständiger Vertrag; Asymmetrische Information; Verhandlungstheorie; Betriebliche Investitionspolitik; Eigentumsrechtstheorie; Theorie